Polycentric groundwater governance: insights from the Kavango-Zambezi Transfrontier Conservation Area - Mukuyu, P.; Nyambe, N.; Magombeyi, Manuel Simba; Ebrahim, Girma Yimer (Ubiquity Press, Ltd., 2024)
This paper analyses groundwater governance within a transfrontier conservation landscape. Given the current heightened interest in groundwater development, it is imperative that more thought be given to how groundwater resources can best be managed in different contexts for multiple uses and users. Transfrontier conservation areas are areas of vast biological diversity whose functioning and ecosystem integrity depends on the availability of water to sustain ecosystems and subsequently derive economic benefit. Further, climate vulnerable rural communities depend on and form an important part of this landscape. The work highlighted in this paper is based on a study conducted in parts of the Kavango-Zambezi Transfrontier Conservation Area (TFCA), the largest TFCA in the world. Climate induced challenges such as droughts and general poor land use planning have resulted in threats to long term sustainability of freshwater ecosystems and increased incidences of human-wildlife conflicts over limited water resources. Effective groundwater governance can potentially provide pathways for alleviating these challenges.